Governance Analysis: Accountability and Transparency in Mount Lewotobi Disaster Management - Afifah Fauzah Lathifah; Markus A.K.B Hallan; Filipus Argentano Guntur Suryaputra (Asian Journal of Management Analytics, 2026)
This study analyzes the governance of Unforeseen Expenditures (BTT) during the Mount Lewotobi eruption in East Flores Regency. Employing a qualitative case study with stewardship theory, data were gathered through documentary analysis and semi-structured interviews with regional disaster agency (BPBD) and village officials. The findings reveal a governance paradox: internal administrative accountability is rigorously enforced through an eleven-tier document verification system, yet public transparency is heavily constrained. Financial data in the digital system (SIPD) is highly aggregated, while field-level information depends on manual ledgers and village loudspeakers, causing severe information asymmetry for independent evacuees. This research implies a critical need to transition emergency financial reporting toward open, interactive digital transparency.